The Use of Flow Cytometry for Estimating Genome Sizes and DNA Ploidy Levels in Plants - Loureiro, João; Čertner, Martin; Lučanová, Magdalena; Sliwinska, Elwira; Kolář, Filip; Doležel, Jaroslav; Garcia, Sònia; Castro, Sílvia; Galbraith, David W (Methods in molecular biology (Clifton, N.J.), 2023)
Flow cytometry has emerged as a uniquely flexible, accurate, and widely applicable technology for the analysis of plant cells. One of its most important applications centers on the measurement of nuclear DNA contents. This chapter describes the essential features of this measurement, outlining the overall methods and strategies, but going on to provide a wealth of technical details to ensure the most accurate and reproducible results. The chapter is aimed to be equally accessible to experienced plant cytometrists as well as those newly entering the field. Besides providing a step-by-step guide for estimating genome sizes and DNA-ploidy levels from fresh tissues, special attention is paid to the use of seeds and desiccated tissues for such purposes. Methodological aspects regarding field sampling, transport, and storage of plant material are also given in detail. Finally, troubleshooting information for the most common problems that may arise during the application of these methods is provided.
Keywords: rostliny; buněčné jádro; Flow cytometry; Genome, Plant; průtoková cytometrie; délka genomu; Plant tissues; genom rostlinný; Genome Size; Seeds; Best practices; Plants; Plant nuclei isolation; DNA, Plant; Flow Cytometry; Desiccated tissues; ploidie; Cell Nucleus; Ploidies; DNA rostlinná; DAPI; Propidium iodide; Genome size; DNA-ploidy level